Words Are Stones: Countering Hate Speech Among Young Generations in Europe. - Fontefrancesco, Michele Filippo (Corporación Universitaria Minuto de Dios - UNIMINUTO, 2021)
While the Media and Information Literacy (MIL) City’s framework highlights the objectives of global social inclusion using digital tools and resources, the phenomenon of online hate speech poses a grave threat. To provide policymakers, professionals, and educators with fresh insight into this phenomenon; this chapter presents the results of the research conducted within the European project “Words are Stones.” Through a campaign of focus groups conducted in eight European countries (Bulgaria, Czech Republic, Greece, Hungary, Lithuania, Italy, Romania, and Spain) in 2018; the research highlighted the low level of digital awareness and scarce digital empathy that characterize the use of digital media among young adults. These elements create fertile ground for hate speech. To build functional MIL cities, this chapter advocates for new initiatives that promote full and mature MIL among so-called digital natives, to help: 1) understand the deep interconnection and interaction between online and offline spaces in everyday life, 2) raise awareness on the phenomenon of hate speech, and 3) explain the contributions that MIL stakeholders, such as families, schools, and NGOs, can have in preventing and alleviating hate speech.
Capítulo 8 - MIL Cities and MIL Citizens: Informed, Engaged, Empowered by Media and Information Literacy (MIL).
Keywords: Hate speech; Focus groups interview; Digital inclusion